The production of knowledge of consumption: the development and organization of market research industry in Turkey - Pektaş, Şerafettin. (Thesis (M.A.)-Bogazici University. Graduate Institute of Social Sciences, 2005., 2005)
This study aims at analyzing the emergence, development, organization and social impacts of market research industry in Turkey from a sociological perspective. With the global transformations altered the operation of capitalism worldwide since early 1970s and Turkey's articulation to this process through neo-liberal domestic transformations, consumption has become more visible in daily life. Market research industry has been a neglected area for social scientists though its sociological relevance in understanding the consumption sphere. Therefore, this study attempts to comprehend the development and institutionalization of market research as a new social force assisting to the organization and manipulation of consumption sphere in Turkey since 1980s. In so doing, the market research industry is analyzed in three dimensions: First dimension contextualizes the emergence, development, organization and operation of market industry in Turkey in a historical and structural map. Second dimension, after analyzing the rise of knowledge generation as a new source of wealth creation and as an inevitable competitive advantage, explores the construction of market research as a separate field in which a special kind of bounded knowledge is being produced. The third dimension is about lifestyle studies undertaken by market researchers which in turn enable us, on the one hand, to understand the indirect role of market research industry in the organization of consumption sphere; on the other hand, to examine the relationship between consumption activities and identity formation given the fact that there is a growing literature on this relationship, especially since 1980s.
Keywords: Marketing research.